Tobacco use in health-science students - Prat-Marin, Andres; Fuentes-Almendras, M.M.; Sanz-Gallen, P.; Canela-Argues, R.; Canela-Soler, J.; Pardell-Alenta, H.; Salleras-Sanmarti, L.L. (Revista de Saúde Pública, 1994)
The characteristics of tobacco use by students of the Division of Health Sciences of the University of Barcelona have been studied. During the 1988-1989 school year, 382 students were individually interviewed about their use of tobacco by means of a questionnaire routinely used by the Department of Health and Social Security of the Generalitat of Catalonia (Spain), with pertinent modifications for this specific group. These interviews were performed by appropriately trained personnel. Information was also gathered on the influence of university-level studies on smoking habits, the effect of advertising and the efficacy of antitobacco programs and campaigns carried out by the government. The study sample was drawn from lists supplied by the registrars' offices, by means of a random sampling by school (Medicine, Pharmacy, Psychology, Odontology and Nursing). The prevalence of tobacco use was 40.8% (29.8% daily smokers and 11% occasional smokers). These results are similar to those described in the literature, although these values are somewhat higher than those in more developed countries with a longer tradition of resistance to the use of tobacco. It is important to note that studying health sciences does not appera to be a major influence on the student's habits, but that the social and cultural environment is the factor which weighs the most in this respect. In conclusion, to reduce the prevalence of tobacco use in this important group, educational programs must be begun at the pre-university level (secundary school) and changes should be made in the curricula of the health professional so that areas related to tobacco use are more motivational for students.